How does Emotional Salary Influence Job Satisfaction? A Construct to be Explored - Díaz-García, Gustavo; Almorza-Gomar, David; González-Arrieta, Gerson (ANDULI, Revista Andaluza de Ciencias Sociales, 2023)
The objective of this research is to explore the empirical link between the dimensions of emotional salary and job satisfaction in the time of COVID-19, statistical studies of which are quite scarce in the environment of emerging markets. To address this gap in the literature, a survey of 190 executives of companies in Costa Rica was done during the first half of 2021. This analysis uses a multiple hierarchical model and structural equations to empirically demonstrate that the creation of value dimension, the strategic dimension, the motivational dimension and the human dimension of the emotional salary construct of Quintero and Betancur affect the job satisfaction dimension of Costa Rica’s human capital. The results show that there is a significant relationship between each of the aforementioned dimensions of emotional salary and the dimension of job satisfaction.